2011
DOI: 10.1093/scan/nsr084
|View full text |Cite
|
Sign up to set email alerts
|

Increased anterior cingulate cortex and hippocampus activation in Complex PTSD during encoding of negative words

Abstract: Post-traumatic stress disorder (PTSD) is associated with impaired memory performance coupled with functional changes in brain areas involved in declarative memory and emotion regulation. It is not yet clear how symptom severity and comorbidity affect neurocognitive functioning in PTSD. We performed a functional magnetic resonance imaging (fMRI) study with an emotional declarative memory task in 28 Complex PTSD patients with comorbid depressive and personality disorders, and 21 healthy non-trauma-exposed contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
109
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(121 citation statements)
references
References 77 publications
5
109
2
3
Order By: Relevance
“…These are both cognitive mechanisms implicated in the maintenance of PTSD (38,51). The ADCYAP1R1 polymorphism did not influence interactions between the amygdala and ventromedial prefrontal cortex, despite the fact that dysregulated amygdala-prefrontal circuits are central neural features of PTSD (52,53).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…These are both cognitive mechanisms implicated in the maintenance of PTSD (38,51). The ADCYAP1R1 polymorphism did not influence interactions between the amygdala and ventromedial prefrontal cortex, despite the fact that dysregulated amygdala-prefrontal circuits are central neural features of PTSD (52,53).…”
Section: Discussionmentioning
confidence: 79%
“…Synaptic plasticity in the hippocampus is also critical to the formation and retrieval of conscious memories of personal experiences [episodic memory (37)]. Changes in hippocampal function are often observed in anxiety disorders, with several studies showing increased hippocampal activation in PTSD (38-41), hypothesized to reflect additional memory encoding or retrieval processes (38,40). The hippocampus is particularly sensitive to stress hormones, which can impair plasticity (42, 43); significant early life stress, often in the form of childhood maltreatment, has been closely linked to reductions in hippocampal plasticity (44).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been found that patients with PTSD have reduced hemodynamic responses in the medial prefrontal cortex (21), which fits with the idea that decreased prefrontal activity, through amygdala disinhibition, could lead to increased formation of traumatic memories and predispose to PTSD. However, another study found that encoding of later remembered negative words vs. baseline was associated with increased activations in the cingulate cortex and dorsomedial prefrontal cortex in complex PTSD compared with healthy controls (22). Moreover, a recent study has demonstrated that damage to the medial prefrontal cortex protects against PTSD (23).…”
Section: Discussionmentioning
confidence: 99%
“…Three other dot probe studies observed an increased vlPFC response to threatening facial expressions: two revealed corresponding associations between anxiety and threat bias (Britton, et al, 2011; Monk, et al, 2006), and the third found no significant anxiety-related differences in threat bias, measured behaviorally (Monk, et al, 2008). Increased vlPFC activation to distracting emotional information has been observed in selective attention (Yamasaki, et al, 2002) and response inhibition (Chiu, Holmes, & Pizzagalli, 2008) studies of healthy individuals, as well as working memory (Morey et al, 2008; Thomaes et al, 2011) studies of PTSD populations. Ventrolateral prefrontal regions have extensive connections with limbic areas, including the amygdala (Petrides & Pandya, 2002), and clearly participate in the processing of threatening or aversive cues; however, the functional role of the vlPFC in this network requires further clarification.…”
Section: Discussionmentioning
confidence: 99%